Brain structural and functional changes during menstrual migraine: Relationships with pain - Wang, Zi-wen; Yin, Zi-han; Wang, Xiao; Zhang, Yu-tong; Xu, Tao; Du, Jia-rong; Wen, Yi; Liao, Hua-qiang; Zhao, Yu; Liang, Fan-rong; Zhao, Ling (Frontiers in Molecular Neuroscience, 2022)
Objectives: Menstrual migraine (MM) is a special type of migraine associated with the ovarian cycle, which imposes a marked burden on female patients. However, the pathogenesis of MM is not completely understood. We investigated gray matter volume (GMV) and functional connectivity (FC) alterations in MM patients to explore whether there are changes in resting-state FC (rsFC) in brain regions with structural abnormalities and investigated their relevance to pain and concomitant symptoms. Methods: Seventy-five MM patients and 54 female healthy controls (HCs) underwent functional magnetic resonance imaging and examination, while MM patients also completed a patient’s headache diary, which included the frequency of migraine attacks, visual analogue scale (VAS) for pain, self-rating anxiety scale, and self-rating depression scale (SDS). We used voxel-based morphometry (VBM) to examine the GMV differences between the MM and HC groups. Then, the identified brain areas used as seeds to compute their rsFC with other brain regions. The correlations between clinical outcomes and VBM/rsFC alterations were explored. Results: Compared with HCs, patients with MM showed decreased GMV in the right anterior cingulate cortex (ACC) and increased GMV in the right superior parietal cortex. Pearson’s correlation analysis illustrated that only GMV in the right ACC was associated with VAS pain scores. RsFC with the ACC as the seed showed that MM patients exhibited increased FC between the ACC and the left inferior temporal gyrus, bilateral angular gyrus (AG), and right precuneus. Correlation analysis showed that the change in FC between the right ACC and right precuneus was positively correlated with headache frequency, and the change in FC between the right ACC and right AG was positively correlated with the SDS score. Conclusions: Our results reveal that the ACC may be a brain structure involved in MM, and that it demonstrates altered functional alterations with areas involved in pain and emotional-related processes (left inferior temporal gyrus, bilateral AG, and right precuneus) in MM patients. This suggests that abnormalities in the ACC may contribute to the physiological and pathological mechanisms of MM.